2017
DOI: 10.1111/dmcn.13380
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal predictors of cognitive ability in adults born very preterm: a prospective cohort study

Abstract: Aim To identify neonatal predictors to allow a developmental prognosis of the cognitive abilities of survivors born very preterm/very low birthweight (VLBW) into adult life. Method The Bavarian Longitudinal Study is a prospective whole‐population study that followed 260 infants born very preterm/VLBW from birth to adulthood. Regression analyses examined which neonatal factors predicted adult IQ. Results Neonatal morbidity, neonatal treatment, and early social environment of infants born very preterm/VLBW expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 29 publications
7
62
0
2
Order By: Relevance
“…Further, previous findings have shown that early parent-infant relationships predict long-term cognitive outcomes. 33 Our findings support future research to investigate whether targeted intervention programmes to improve early parent-infant relationships and to provide parent support in the NICU can lead to significant and long-term improvements in children's motor development. Given the evidence from previous studies that early motor deficits do not diminish over time, 34 and that poor motor skills in adulthood are associated with mental health problems and lower health-related quality of life, 35 the early motor trajectories identified in this current study may help to predict whether children with high degree of motor difficulties over the first 5 years of life are more likely to have additional problems in other developmental domains across the life span.…”
Section: Discussionsupporting
confidence: 74%
“…Further, previous findings have shown that early parent-infant relationships predict long-term cognitive outcomes. 33 Our findings support future research to investigate whether targeted intervention programmes to improve early parent-infant relationships and to provide parent support in the NICU can lead to significant and long-term improvements in children's motor development. Given the evidence from previous studies that early motor deficits do not diminish over time, 34 and that poor motor skills in adulthood are associated with mental health problems and lower health-related quality of life, 35 the early motor trajectories identified in this current study may help to predict whether children with high degree of motor difficulties over the first 5 years of life are more likely to have additional problems in other developmental domains across the life span.…”
Section: Discussionsupporting
confidence: 74%
“…First, it is possible that owing to advances in medical research, a cohort effect may be evident in our selected studies. 96 However, socio-economic status was not included as a covariate in the current meta-analysis because there is a severe lack of consistency in terms of reporting socio-economic variables across studies. As such, it may follow that cognitive outcomes have also improved in the same time period.…”
Section: Discussionmentioning
confidence: 99%
“…Early parent–infant relationship quality was assessed with the Parent–Infant Relationship Index (PIRI) from birth to 5 months (Breeman, Jaekel, Baumann, Bartmann, & Wolke, ; Wolke, Schmid, Schreier, & Meyer, ). The instrument consists of eight “yes” or “no” items obtained by trained nurses' observations and a standardized interview with the children's parents, assessing attachment‐related parental concerns, feelings, and behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…Early parent-infant relationship quality was assessed with the Parent-Infant Relationship Index (PIRI) from birth to 5 months (Breeman, Jaekel, Baumann, Bartmann, & Wolke, 2017;Wolke, Schmid, Schreier, & Meyer, 2009).…”
Section: Parent-infant Relationship Postnatalmentioning
confidence: 99%